In silico assessment of pharmacotherapy for carbon monoxide induced arrhythmias in healthy and failing human hearts - Jiang, Huasen; Zhang, Shugang; Lu, Weigang; Yang, Fei; Bi, Xiangpeng; Ma, Wenjian; Wei, Zhiqiang (Frontiers in Physiology, 2022)
Background: Carbon monoxide (CO) is gaining increased attention in air pollution-induced arrhythmias. The severe cardiotoxic consequences of CO urgently require effective pharmacotherapy to treat it. However, existing evidence demonstrates that CO can induce arrhythmias by directly affecting multiple ion channels, which is a pathway distinct from heart ischemia and has received less concern in clinical treatment. Objective: To evaluate the efficacy of some common clinical antiarrhythmic drugs for CO-induced arrhythmias, and to propose a potential pharmacotherapy for CO-induced arrhythmias through the virtual pathological cell and tissue models. Methods: Two pathological models describing CO effects on healthy and failing hearts were constructed as control baseline models. After this, we first assessed the efficacy of some common antiarrhythmic drugs like ranolazine, amiodarone, nifedipine, etc, by incorporating their ion channel-level effects into the cell model. Cellular biomarkers like action potential duration and tissue-level biomarkers such as the QT interval from pseudo-ECGs were obtained to assess the drug efficacy. In addition, we also evaluated multiple specific IKr activators in a similar way to multi-channel blocking drugs, as the IKr activator showed great potency in dealing with CO-induced pathological changes. Results: Simulation results showed that the tested seven antiarrhythmic drugs failed to rescue the heart from CO-induced arrhythmias in terms of the action potential and the ECG manifestation. Some of them even worsened the condition of arrhythmogenesis. In contrast, IKr activators like HW-0168 effectively alleviated the proarrhythmic effects of CO. Conclusions: Current antiarrhythmic drugs including the ranolazine suggested in previous studies did not achieve therapeutic effects for the cardiotoxicity of CO, and we showed that the specific IKr activator is a promising pharmacotherapy for the treatment of CO-induced arrhythmias.